Exploring the most discriminative brain structural abnormalities in ASD with multi-stage progressive feature refinement approach - Sun, Bingxi; Xu, Yingying; Kat, Siuching; Sun, Anlan; Yin, Tingni; Zhao, Liyang; Su, Xing; Chen, Jialu; Wang, Hui; Gong, Xiaoyun; Liu, Qinyi; Han, Gangqiang; et al. (Frontiers in Psychiatry, 2024)
Objective: Autism spectrum disorder (ASD) is a neurodevelopmental condition characterized by increasing prevalence, diverse impairments, and unclear origins and mechanisms. To gain a better grasp of the origins of ASD, it is essential to identify the most distinctive structural brain abnormalities in individuals with ASD. Methods: A Multi-Stage Progressive Feature Refinement Approach was employed to identify the most pivotal structural magnetic resonance imaging (MRI) features that distinguish individuals with ASD from typically developing (TD) individuals. The study included 175 individuals with ASD and 69 TD individuals, all aged between 7 and 18 years, matched in terms of age and gender. Both cortical and subcortical features were integrated, with a particular focus on hippocampal subfields. Results: Out of 317 features, 9 had the most significant impact on distinguishing ASD from TD individuals. These structural features, which include a specific hippocampal subfield, are closely related to the brain areas associated with the reward system. Conclusion: Structural irregularities in the reward system may play a crucial role in the pathophysiology of ASD, and specific hippocampal subfields may also contribute uniquely, warranting further investigation.